Effectiveness of gel formulation of mahogany (Swietenia macrophylla) bark extract and its potential as an anti-inflammatory in white male rats (Rattus norvegicus) - SHAFA GEULISTIA NURANI; NAFASYA NEGIY DELUNA; PUTRI NABILA; SYAMSUL FALAH (Nusantara Bioscience, 2022)
Abstract. Nurani SG, Deluna NN, Nabila P, Falah S. 2022. Effectiveness of gel formulation of mahogany (Swietenia macrophylla) bark extract and its potential as an anti-inflammatory in white male rats (Rattus norvegicus). Nusantara Bioscience 14: 117-121. Mahogany bark contains phytochemical compounds that have anti-inflammatory activity. This study aims to determine the anti-inflammatory activity of mahogany-bark extract gel formulation in-vivo. Gel formulations of 96% ethanol extract of mahogany bark at different concentrations were tested for anti-inflammatory activity on the paws of rats induced by 1% carrageenan. The data observed were the thickness of the foot edema of rats. Positive control was anti-inflammatory drugs (Desoximetasone), and negative control was the gel formulation without extract. Data on the thickness of rat paw edema were analyzed using the ANOVA test. The results of the anti-inflammatory test showed that gel formulation 2 with an extract concentration of 10% had a thickness reduction value of 41.83%, which was not significantly different from the positive control treatment of 44.38%. The results of the dispersion test showed that formulation 2 and formulation 3 had good dispersibility, as suggested in SNI, and all gel formulations had good adhesion. Based on these results, it was concluded that formulation 2 was the most effective in reducing rat paw edema.